Storage and the Use of Peroxydase Enzyme to Detect Germination Capability of Sandoricum koetjape Merr. Seeds- A Neglected Tropical Fruit Species - USEP SOETISNA; DODY PRIADI; SRI HARTATI; ENNY SUDARMONOWATI (Society for Indonesian Biodiversity, 2005)
Sandoricum koetjape which belongs to the group of mahogany, possesses seeds with sticky white aril, is a neglected local fruit species that might extinct if conservation efforts are not made. Besides preserving the embryos and embryonic axis on different periods of storage (0, 3, 5, 7 days) on a vacuum glass container containing silica gel, the latter organs were also preserved in liquid nitrogen to study the possibility of long-term storage. The water content of the preserved organs was measured in relation to the length of storage and the germination rate. To determine the role of peroxidase in the germination rate of preserved zygotic embryos, the level of peroxidase was measured. Seeds of control and of 3-day storage were mostly germinated at day-6. The average rate of germination was reduced to 23.33% when the seeds were desiccated with silica gel for 7 days which resulted in 27.69% water content. This germination capability and the length of hypocotyls seem to correlate with peroxidase activity in the seeds. In general, the higher the percentage of germination, the longer the length of hypocotyls, the higher the peroxidase activity, except for seeds desiccated for 7 days. The range of peroxidase activity was 6.81-3856.20 Î”A/2min/mg. When the seeds were desiccated for 7 days, they still could germinate at day-18 which indicated by a very high peroxidase activity. Peroxidase activity assay could detect the viability within 15 seconds while the TTZ requires 15 minutes. Although the highest percentage of survived embryonic axis after storage in liquid nitrogen was only 23.42%, the results showed that soaking in 10-20% DMSO for 20 minutes of prerequisite as without DMSO led to no survival. These results offer an alternative procedure to detect the germination ability of seeds at early stage and longer period of preservation which could contribute to future ex situ conservation.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: recalcitrant, seeds, embryos, desiccation, preservation, peroxidase, Sandoricum koetjape.